Q. 53.6( 28 Votes )

# If x - √5 is a factor of the cubic polynomial x^{3} - 35x^{2} + 13x - 35, then find all the zeroes of the polynomial.

Answer :

Let P(x) = x^{3} - 35x^{2} + 13x - 35

As √5 is one of the zeroes of P(x).

⇒ (x - √5) is one of the factors of P(x).

Dividend = (divisor) (quotient) + remainder

⇒ p(x) = g(x).q(x) + r(x)

⇒ x^{3} - 35x^{2} + 13x - 35 = (x - √5) (x^{2} - 2√5x + 3) + 0

x^{3} - 35x^{2} + 13x - 35 = 0

= (x - √5) (x^{2} - 2√5x + 3) = 0

= (x - √5) [x^{2} - {(√5 + √2) x + (√5 - √2) x} + 3) = 0

= (x - √5) [x{x - (√5 + √2)} - (√5 - √2) {x - (√5 + √2)} + 3] = 0

= (x - √5) {x - (√5 + √2)} {x - (√5 - √2)} = 0

⇒ x = (√5 + √2), (√5 - √2), √5

Rate this question :

Divide the polynomial p(x) by the polynomial g(x) and find the quotient q(x) and remainder r(x) in each case :

p(x) = x^{3} – 3x^{2} + 4x + 2 , g(x) = x – 1

Divide the polynomial p(x) by the polynomial g(x) and find the quotient q(x) and remainder r(x) in each case :

p(x) = x^{3} – 3x^{2}– x + 3, g(x) = x^{2} – 4x + 3

When a polynomial p(x) is divided by (2x + 1), is it possible to have (x - 1) as a remainder? Justify your answer.

RS Aggarwal - MathematicsDivide the polynomial p(x) by the polynomial g(x) and find the quotient q(x) and remainder r(x) in each case :

p(x) = x^{4} + 2x^{3} – 3x^{2} + x – 1, g(x) = x – 2

Find all the zeroes of the polynomial given below having given numbers as its zeroes.

x^{4} – 6x^{3} – 26x^{2} + 138x – 35;2±√3

p(x) = x^{6} + 3x^{2} + 10 and g(x) = x^{3} + 1

p(x) = x^{4} + 1, g(x) = x + 1

Verify that are the zeroes of the cubic polynomial p(x) = 3x^{2} – 5x^{2} – 11x – 3 and then verify the relationship between the zeroes and the coefficients.

Find all the zeros of the polynomial, if two of its zeros are √3 and .

RD Sharma - Mathematics